Role of sperm apoptosis and oxidative stress in male infertility: A narrative review - Asadollah Asadi; Rozita Ghahremani; Arash Abdolmaleki; Farzad Rajaei (Shahid Sadoughi University of Medical Sciences, 2021)
Abstract Activation of caspase, externalization of phosphatidyl serine, change in the mitochondrial membrane potential, and DNA fragmentation are apoptosis markers found in human ejaculated spermatozoa. Also, reactive oxygen species (ROS) play a vital role in the different types of male infertility. In this review, data sources including Google Scholar, Scopus, PubMed, and Science Direct were searched for publications with no particular time restriction to get a holistic and comprehensive view of the research. Apoptosis regulates the male germ cells, correct function and development from the early embryonic stages of gonadal differentiation to fertilization. In addition to maintaining a reasonable ratio between the Sertoli and germ cells, apoptosis is one of the well-known quality control mechanisms in the testis. Also, high ROS levels cause a heightened and dysregulated apoptotic response. Apoptosis is one of the well-known mechanisms of quality control in the testis. Nevertheless, increased apoptosis may have adverse effects on sperm production. Recent studies have shown that ROS and the consequent oxidative stress play a crucial role in apoptosis. This review aims to assimilate and summarize recent findings on the apoptosis in male reproduction and fertility. Also, this review discusses the update on the role of ROS in normal sperm function to guide future research in this area.